Prevention of childhood obesity through motivation to physical activity - Carrillo Aguilera, Sonia; Molero López-Barajas, David; Zagalaz Sánchez, Mª Luisa; Morente Oria, Honorato (FEADEF, 2012)
This paper aims to review the current worrying situation in terms of physical activity in our country and the problem that leads us to be below the European average, with the attendant problems of obesity, particularly among children, which follow from this. We analyzed the intervention programs that are being used as PIOBIN plan (The Andalusian Plan for Childhood Obesity), effective from 2007-12, based on a national strategy called Naos Strategy and how different studies support that some intrinsic motivation toward physical activity helps to create lasting habits to the practice. We also carry out an analysis of the different Motivation theories and we base our study on the Self-determination Theory of Deci and Ryan (1985, 2000)